Answer:
hope it helps mark as brainliest
<h3>
Answer: (n-1)^2</h3>
This is because we have a list of perfect squares 0,1,4,9,...
We use n-1 in place of n because we're shifting things one spot to the left, since we start at 0 instead of 1.
In other words, if the answer was n^2, then the first term would be 1^2 = 1, the second term would be 2^2 = 4, and so on. But again, we started with 0^2 = 0, so that's why we need the n-1 shift.
You can confirm this is the case by plugging n = 1 into (n-1)^2 and you should find the result is 0^2 = 0. Similarly, if you tried n = 2, you should get 1^2 = 1, and so on. It appears you already wrote the answer when you wrote "Mark Scheme".
All of this only applies to sequence A.
side note: n is some positive whole number.
Answer:
(1, 6 )
Step-by-step explanation:
5x + 2y = 17 → (1)
4x + y = 10 → (2)
Multiplying (2) by - 2 and adding to (1) will eliminate the y- term
- 8x - 2y = - 20 → (3)
Add (1) and (3) term by term to eliminate y
- 3x + 0 = - 3
- 3x = - 3 ( divide both sides by - 3 )
x = 1
Substitute x = 1 into either of the 2 equations and solve for x
Substituting into (1)
5(1) + 2y = 17
5 + 2y = 17 ( subtract 5 from both sides )
2y = 12 ( divide both sides by 2 )
y = 6
solution is (1, 6 )
It’s is b why u covering your camera lol